On the road with WRAP53β: guardian of Cajal bodies and genome integrity - Henriksson, Sofia; Farnebo, Marianne (Frontiers in Genetics, 2015)
The WRAP53 gene encodes both an antisense transcript (WRAP53α) that stabilizes the tumor suppressor p53 and a protein (WRAP53β) involved in maintenance of Cajal bodies, telomere elongation and DNA repair. WRAP53β is one of many proteins containing WD40 domains, known to mediate a variety of cellular processes. These proteins lack enzymatic activity, acting instead as platforms for the assembly of large complexes of proteins and RNAs thus facilitating their interactions. WRAP53β mediates site-specific interactions between Cajal body factors and DNA repair proteins. Moreover, dysfunction of this protein has been linked to premature aging, cancer and neurodegeneration. Here we summarize the current state of knowledge concerning the multifaceted roles of WRAP53β in intracellular trafficking, formation of the Cajal body, DNA repair and maintenance of genomic integrity and discuss potential crosstalk between these processes.